PEMBERDAYAAN EKONOMI MASYARAKAT DUSUN KRAJAN DESA GUMIRIH KECAMATAN SINGOJURUH MELALUI APOTIK HIDUP PROGRAM POSDAYA BERBASIS MASJID - Al Muftiyah (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2020)
The mosque is a place that functioned to build the integrity of the congregation ties in the spirit of ‘Gotong Royong’ to realize the common welfare. Based on the potential environment around the mosque ' Baiturrahman', where there is a wide vacant land then this program aims to empower the community in the economic sector with the promotion of the planting and processing of life pharmacies. The implementation of the mosque-based Pospower thematic program has been carried out and reached 100%. The results of activities can be described as follows: 1) There are a number of living pharmacy plants that are empowered around the mosque as the main ingredient of processed products; 2) There are several home industry that make the processed pharmacies products live into traditional herbal packaging; 3) There are several small shops that belong to the residents who sell live pharmacies; 4) There are several online shops owned by residents who sell live pharmacies.